2018
DOI: 10.1002/cam4.1503
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of epidemiological features, clinicopathological features, and treatments between premenopausal and postmenopausal female breast cancer patients in western China: a retrospective multicenter study of 15,389 female patients

Abstract: Premenopausal and postmenopausal breast cancers are considered different types. Thus, this study aimed to explore differences in risk factors, epidemiological features, clinicopathological features, and treatment modes of premenopausal breast cancer compared to postmenopausal patients in western China. This was a hospital‐based, retrospective, multicenter epidemiological study of patients with breast cancer. Using the Western China Clinical Cooperation Group database, we obtained the records of 15,389 female b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
20
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
(47 reference statements)
7
20
2
Order By: Relevance
“…Patients with premenopausal breast cancer constituted 54.9% of all patients in our study. Similar rates were found in studies conducted in Asia, at 54.3-54.55% [17, 18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Patients with premenopausal breast cancer constituted 54.9% of all patients in our study. Similar rates were found in studies conducted in Asia, at 54.3-54.55% [17, 18].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, OR positivity was high in both premenopausal women and postmenopausal women. OR positivity was 68.94% in the premenopausal group and 54.92% in the postmenopausal group; Feng et al found 59% in the premenopausal group and 55% in the postmenopausal group in their study [17]. In the premenopausal group, OR+ PR+ patients were at a higher rate, whereas in the postmenopausal group OR– PR– patients were higher.…”
Section: Discussionmentioning
confidence: 92%
“…Ma et al reported that the age of menarche among healthy urban Chinese girls decreased from 13.5 years in 1979 to 12.27 years between 2003 and 2005. [ 25 ] Age at menarche (>13 years compared with ≤13 years) was not found to be a risk factor after adjusting for all the variables with differences in the single logistic regression analysis in our study. Studies over the past several decades have indicated that individuals living in less-developed areas often had poorer general health than individuals living in relatively developed areas.…”
Section: Discussioncontrasting
confidence: 56%
“…The reasons behind these findings are various and complex and include diversity in tumour genetics, cultural and demographic variables, as well as differences in health policies [3, 5, 6]. Although the incidence rates of breast cancer in Asia are lower than in western countries, they have been increasing recently [3, 7-9]. The rapid increase in the incidence of the disease is a reason for concern in China, especially in urban areas [10].…”
Section: Introductionmentioning
confidence: 99%